Andersen–Tawil Syndrome With Novel Mutation in KCNJ2: Case Report - Yim, Jisook; Kim, Kyoung Bo; Kim, Minsun; Lee, Gun Dong; Kim, Myungshin (Frontiers in Pediatrics, 2022)
Andersen-Tawil syndrome (ATS) is a rare autosomal dominant disorder characterized by a classic symptom triad: periodic paralysis, ventricular arrhythmias associated with prolonged QT interval, and dysmorphic skeletal and facial features. ATS is caused by a pathogenic variant of the inwardly rectifying potassium channel subfamily J member 2 (KCNJ2) gene. Herein, we report a novel KCNJ2 causative variant in a proband and her father showing different ATS-associated symptoms. A 15-year-old girl was referred because of episodic weakness and periodic paralysis in both legs for 2–3 months. The symptoms either occurred when she was tired or after strenuous exercise. These attacks made walking or climbing stairs difficult and lasted from one to several days. She had a short stature (142 cm, <3rd percentile) and weighed 40 kg. The proband also showed orbital hypertelorism, dental crowding, mandibular hypoplasia, fifth-digit clinodactyly, and small hands. Scoliosis in the thoracolumbar region was detected by chest X-ray. Since she was 7 years old, she had been treated for arrhythmia associated long QT interval and underwent with periodic echocardiography. Brain MRI revealed cerebrovascular abnormalities indicating absence or hypoplasia of bilateralinternal carotid arteries, and compensation of other collateral vessels was observed. There were no specific findings related to intellectual development. The proband's father also had a history of periodic paralysis similar to the proband. He did not show any cardiac symptoms. Interestingly, he was diagnosed with hyperthyroidism during an evaluation for paralytic symptoms. Clinical exome sequencing revealed a novel heterozygous missense variant: Chr17(GRCh37):g.68171593A>T, NM_000891.2:c.413A>T, p.(Glu138Val) in KCNJ2 in the proband and the proband's father.